A novel Pik allele confers extended resistance to rice blast - Qi, Zhongqiang; Meng, Xiuli; Xu, Ming; Du, Yan; Yu, Junjie; Song, Tianqiao; Pan, Xiayan; Zhang, Rongsheng; Cao, Huijuan; Yu, Mina; Telebanco-Yanoria, Mary Jeanie; Lu, Guodong; et al. (Wiley, 2024)
In the ongoing arms race between rice and Magnaporthe oryzae, the pathogen employs effectors to evade the immune response, while the host develops resistance genes to recognise these effectors and confer resistance. In this study, we identified a novel Pik allele, Pik‐W25, from wild rice WR25 through bulked‐segregant analysis, creating the Pik‐W25 NIL (Near‐isogenic Lines) named G9. Pik‐W25 conferred resistance to isolates expressing AvrPik‐C/D/E alleles. CRISPR‐Cas9 editing was used to generate transgenic lines with a loss of function in Pik‐W25‐1 and Pik‐W25‐2, resulting in loss of resistance in G9 to isolates expressing the three alleles, confirming that Pik‐W25‐induced immunity required both Pik‐W25‐1 and Pik‐W25‐2. Yeast two‐hybrid (Y2H) and split luciferase complementation assays showed interactions between Pik‐W25‐1 and the three alleles, while Pik‐W25‐2 could not interact with AvrPik‐C, ‐D, and ‐E alleles with Y2H assay, indicating Pik‐W25‐1 acts as an adaptor and Pik‐W25‐2 transduces the signal to trigger resistance. The Pik‐W25 NIL exhibited enhanced field resistance to leaf and panicle blast without significant changes in morphology or development compared to the parent variety CO39, suggesting its potential for resistance breeding. These findings advance our knowledge of rice blast resistance mechanisms and offer valuable resources for effective and sustainable control strategies.